The public health effects of interventions similar to basic income: a scoping review. (March 2020) - Gibson, Marcia; Hearty, Wendy; Craig, Peter
Summary: Universal, unconditional basic income is attracting increasing policy and academic interest. Income is a key health determinant, and a basic income could affect health through its effect on other determinants, such as employment. However, there is little evidence of its potential effects on public health, because no studies of interventions which meet the definition of basic income have been done. However, there is evidence from studies of interventions with similarities to basic income. Therefore, we aimed to identify these studies and to consider what can be learned from them about the potential effects of such interventions on health and socioeconomic outcomes. We did a systematic scoping review of basic income-like interventions, searching eight bibliographic and eight specialist databases from inception to July, 2019, with extensive hand searching. We included publications in English of quantitative and qualitative studies done in upper-middle-income or high-income countries, of universal, permanent, or subsistence-level interventions providing unconditional payments to individuals or families. We sought to identify the range of outcomes reported by relevant studies, and report health, education, employment, and social outcomes. We extracted and tabulated relevant data and narratively reported effects by intervention and outcome. We identified 27 studies of nine heterogeneous interventions, some universal and permanent, and many evaluated using randomised controlled trials or robust quasi-experimental methods. Evidence on health effects was mixed, with strong positive effects on some outcomes, such as birthweight and mental health, but no effect on others. Employment effects were inconsistent, although mostly small for men and larger for women with young children. There was evidence of spill-over effects in studies measuring effects on large populations. In conclusion, little evidence exists of large reductions in employment, and some evidence suggests positive effects on some other outcomes, including health outcomes. Evidence for macro-level effects is scarce. Quasi-experimental and dynamic modelling approaches are well placed to investigate such effects.